Navigating Modernity and Tradition: Strategic Practices in Islamic Schools at The West Kalimantan-Malaysia Border - Misdah, Misdah; Soemantri, Asep Iwa; Syahbudi, Syahbudi; Wajdi, Muh Barid Nizarudin (Jurnal Ilmiah Peuradeun, 2025)
This study explored the strategic management practices adopted by Kyai in Islamic boarding schools along the West Kalimantan-Malaysia border, focusing on overcoming challenges posed by geographical isolation and limited resources. Employing a qualitative case study methodology, interviews were conducted with key stakeholders, including Kyai, Ustadz, and Madrasah Heads, to gather insights into their strategic management approaches. The findings indicated that Kyai plays a pivotal role in institutional growth through systematic strategic planning, which includes conducting SWOT analyses, developing strategic documents, and ensuring structured implementation. The study highlighted how effective leadership and strategic planning are crucial in driving institutional transformation and sustainability in resource-constrained settings, demonstrating the dynamic adaptation of traditional educational models to modern educational demands. The implications of this research suggest that adapting traditional educational frameworks to contemporary management practices enhances institutional capabilities to navigate modern educational and socio-economic challenges, providing a model for similar educational institutions in resource-limited settings.